Developing disease-resistant cattle for Africa—Summary - International Livestock Research Institute (International Livestock Research Institute, 2013)
Livestock trypanosomiasis harms rural family incomes as well as Africa's economic development as a whole. In 2010, the International Livestock Research Institute (ILRI) and partners started a research project to breed cattle resistant to the disease. This 3 minute film summarizes the story of the project, the science, and the potential benefits.